Microstructure homogenization of laser powder bed fusion support-free low angle IN718 walls through heat treatment - Minsol Park; Mudit Kesharwani; Mohammad Attarian Shandiz; Mathieu Brochu (Additive Manufacturing Letters, 2025)
This study investigates the effectiveness of heat treatment (HT) to homogenize the microstructural and mechanical asymmetry between the bulk and the downskin regions of support-free IN718 walls fabricated at angles of 30°, 20°, 15°, and 10° In the as-built condition, the microhardness ranged from 340 ± 5 HV to 351 ± 4 HV for the bulk and from 315 ± 4 HV to 323 ± 10 HV for the downskin region, resulting in a maximum difference range of 35 HV. The HT eliminated this difference where microhardness values of 482 ± 3 HV in the bulk and 478 ± 4 HV in the downskin were measured. The HT induced γ″ precipitation with volume fraction and mean precipitate size in the bulk of 16.6 % and 24.7 ± 7.3 nm. These values are statistically comparable to those in the downskin: 15.8 % and 26.5 ± 7.9 nm. The similarity in the γ″ characteristics explains the recovery of the mismatch in hardness as γ″ contributes approximately 85 % of the strengthening in the HT condition.